The Elephant in The Room: Human-Elephant Conflict in Central District, Botswana - Munamati, Kakale (Department of Environmental and Geographical Science, 2023)
Human-Elephant Conflict is a topic of conservation and socio-economic concern in light of its impacts on elephants and humans alike. The phenomenon has been occurring since the 19th century in Asia and Africa. Land use changes and human expansion into previous wildlife strongholds has exacerbated and increased Human-Elephant Conflict notwithstanding the impacts of an increase in the human population worldwide. Human-Elephant Conflict usually occurs in areas adjacent to protected areas with little know of the nature of Human-Elephant Conflict in areas which are not located near protected areas. Mmashoro Village and surrounding farms are an example of an area that is not located adjacent to a protected area but that is still exposed to Human-Elephant Conflict. The nature of Human-Elephant Conflict in Mmashoro village and surrounding farms consists of damage to fences, JoJo tanks and private gardens. Human-Elephant Conflict in Mmashoro village and surrounding areas has also been increasing over time. Human-Elephant Conflict in Mmashoro village and surrounding farms has varying (in degree and extent) impacts on the financial and emotional livelihoods of farm owners, farm workers, and local residents. This study found that the management strategies employed by the Government of Botswana to mitigate impacts of Human-Elephant Conflict were found to be inhibiting and restricting the livelihoods of all stakeholders. The interventions pursued by the government were, therefore, not enabling the present and future potential livelihoods of all stakeholders while also disadvantaging and prejudicing other stakeholders such as Local Residents and Farm Workers. The results of this study therefore indicate that Mmashoro village and surrounding farms present as an interesting case study as the site is not located next to protected areas as is the case with various conflict regions. As such, this study found that more nuanced and adapted management strategies were needed to ensure that government interventions were effective in areas such as Mmashoro Village and surrounding farms. Further studies are needed in sites which are not located next to protected areas but where Human-Elephant Conflict still occurs albeit haphazardly. Such studies will help to highlight the varied approaches often needed in the different geographical and social regions even though such approaches are often disregarded.